Rate errors in sprayer turning and circular movements: PWM valve as compensation system and why spray boom size matters - Carreira, Vinicius dos Santos [UNESP]; Pereira da Silva, Rouverson [UNESP] (Elsevier, 2022)
Variations in pesticide application can comprise the efficacy. Among them, turning and circular movements (TCM) generate rate errors, harming the crop and environment. Nozzle speeds are different across the spray boom when the sprayer travels through these trajectories, and this affects the treated area by each one. The solution available is the pulse-width modulation valve (PWM), which controls rate by duty cycle. However, there are no comprehensive recommendations and evaluations on the use of this component related to the spray boom size. Therefore, we created a broad simulation of TCM and spray boom size-PWM relationship to evaluate the rate errors. We used simplified equations based on uniform circular motion and previous studies to calculate nozzle speed and target rate. Four circumference radii (25 m, 65 m, 105 m and 150 m) and spray boom width (18 m, 36 m, 42 m, and 50 m) were evaluated to spray 100 L ha−1. In addition, we inserted PWM valves as a rate compensation mechanism and adapted the duty cycle for each situation. As a result, larger spray booms generated higher rate errors and variation, principally in small radii TCM. Thus, in better scenario (Bw 18 m x Rc 150 m) the higher rate error and coefficient of variation were 6.01 L ha−1 and 3.37%, respectively. Conversely, in worst scenario (Bw 50 m x Rc 25 m) the higher error rate and coefficient of variation were 4900 L ha−1 and 225.94%, respectively. There is a downward trend when the circumference radii increases, decreasing the error, as it smoothes the trajectory. Furthermore, PWM valves, individually, are not able to compensate all errors during spraying. There is underdosing and overdosing across the spray boom, which requires not recommended or possible working ranges (<40% or >100%). Thus, it is needed use this technology with other techniques to avoid rate errors during TCM, such as pressure control, simultaneous PWM valves or sensitivity analysis.
Keywords: Flow control; Spray error; Sprayer technologies; Turn compensation